Examining Post-Migration Social Determinants as Predictors of Mental and Physical Health of Recent Syrian Refugees in Canada: Implications for Counselling, Practice, and Research - Kuo, Ben C. H.; Granemann, Lais; Najibzadeh, Avideh; Al-Saadi, Riham; Dali, Monira; Alsmoudi, Bayan (Canadian Journal of Counselling and Psychotherapy, 2020)
In response to the increasing number of Syrian refugees being resettled in Canada and worldwide, the present study set out to explore and examine critical post-migration predictors of mental health and physical health of adult Syrian refugees (n = 235) living in Windsor, Ontario. Using survey data collected from the national SyRIA-lth project and grounded in the Social Determinants of Health model, this study tested demographic, contextual, and psychosocial predictors in two regression models of mental health and physical health, respectively. The results showed that both predictive models were significant in explaining Syrian refugees’ mental and physical health outcomes, as hypothesized. Specifically, age, gender, satisfaction of health services, perceived control, and perceived stress predicted mental health in significant ways, whereas age, satisfaction of health services, and perceived stress predicted physical health in significant ways as well. Implications for practice and research with Syrian refugees, given the identified risk and protective factors of health, are considered.